RETRACTED ARTICLE: N6-methyladenosine induced miR-143-3p promotes the brain metastasis of lung cancer via regulation of VASH1 - Hongsheng Wang; Qianqian Deng; Ziyan Lv; Yuyi Ling; Xue Hou; Zhuojia Chen; Xiaoxiao Dinglin; Shuxiang Ma; Delan Li; Yingmin Wu; Yanxi Peng; Hongbing Huang; et al. (Molecular Cancer, 2019)
Abstract Background Brain metastasis (BM) is one of the principal causes of mortality for lung cancer patients. While the molecular events that govern BM of lung cancer remain frustrating cloudy. Methods The miRNA expression profiles are checked in the paired human BM and primary lung cancer tissues. The effect of miR-143-3p on BM of lung cancer cells and its related mechanisms are investigated. Results miR-143-3p is upregulated in the paired BM tissues as compared with that in primary cancer tissues. It can increase the invasion capability of in vitro blood brain barrier (BBB) model and angiogenesis of lung cancer by targeting the three binding sites of 3’UTR of vasohibin-1 (VASH1) to inhibit its expression. Mechanistically, VASH1 can increase the ubiquitylation of VEGFA to trigger the proteasome mediated degradation, further, it can endow the tubulin depolymerization through detyrosination to increase the cell motility. m6A methyltransferase Mettl3 can increase the splicing of precursor miR-143-3p to facilitate its biogenesis. Moreover, miR-143-3p/VASH1 axis acts as adverse prognosis factors for in vivo progression and overall survival (OS) rate of lung cancer. Conclusions Our work implicates a causal role of the miR-143-3p/VASH1 axis in BM of lung cancers and suggests their critical roles in lung cancer pathogenesis.